2004
DOI: 10.1038/sj.onc.1207576
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of imprinted CDKN1C gene expression is associated with loss of CpG and histone H3 lysine 9 methylation at DMR-LIT1 in esophageal cancer

Abstract: The putative tumor suppressor CDKN1C is an imprinted gene at 11p15.5, a well-known imprinted region often deleted in tumors. The absence of somatic mutations and the frequent diminished expression in tumors would suggest that CDKN1C expression is regulated epigenetically. It has been, however, controversial whether the diminution is caused by imprinting disruption of the CDKN1C/LIT1 domain or by promoter hypermethylation of CDKN1C itself. To clarify this, we investigated the CpG methylation index of the CDKN1C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
(36 reference statements)
4
44
1
Order By: Relevance
“…Because of differences in risk factors, regional incidence is widely variable. It ranges from 5.5 to 14.9 per 100,000 individuals, but it may reach 100 per 100,000 in some regions of [40][41][42][43]. As it will be described below, one of the major mechanisms involved in the down-regulation of p27 and p57 is now believed to be the overexpression of the microRNAs (miRNAs) miR-221/222, which occurs in about 70% of HCCs [44][45][46].…”
Section: Hepatocellular Carcinoma (Hcc) Is One Of the Most Common Canmentioning
confidence: 99%
“…Because of differences in risk factors, regional incidence is widely variable. It ranges from 5.5 to 14.9 per 100,000 individuals, but it may reach 100 per 100,000 in some regions of [40][41][42][43]. As it will be described below, one of the major mechanisms involved in the down-regulation of p27 and p57 is now believed to be the overexpression of the microRNAs (miRNAs) miR-221/222, which occurs in about 70% of HCCs [44][45][46].…”
Section: Hepatocellular Carcinoma (Hcc) Is One Of the Most Common Canmentioning
confidence: 99%
“…Combined bisulfite restriction analyses (COBRA) using the hot-stop method were employed as described previously. 3,4 For H19-DMR, bisulfite sequencing was performed using the same primers as used for COBRA. PCR primers and conditions are shown in Supplementary Table 1.…”
Section: Methylation Analysesmentioning
confidence: 99%
“…We and other groups have previously reported that about 26% of HCCs exhibit a loss of maternal allele methylation at the KvDMR1 imprinted locus at 11p15.5, where CDKN1C/p57 gene is located (Schwienbacher et al, 2000;Diaz-Meyer et al, 2003), and this mechanism has been linked to reduction of CDKN1C/ p57 expression (Soejima et al, 2004). However, in unselected series of HCCs, we have observed a downregulation of CDKN1C/p57 in about 80% of HCCs with reference to matched cirrhosis, therefore CDKN1C/p57 downregulation is likely to rely upon additional molecular mechanisms besides aberrant methylation.…”
Section: Introductionmentioning
confidence: 99%